Somatotype and body composition differences Super League soccer players according to team position - Pehlivan, A.; Odabas, I.; Camliguney, F. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In 2000`s the characteristics of football changed. In 80-90`s a football player was just playing in his position. The position of the player could be known by its body composition. Footballers of our time could play in every position and could take intense training. The aim of this study was to establish the anthropometric and somatotype profiles of elite soccer players according to their playing position, and to determine their relevance for the selection process. Methods: Fourty-Three male soccer players who were members of the professional club participated in this study. Players were classified into the following groups: forwards (n=13), midfielders (n=13), defenders (n=12), and goalkeepers (n=5). Anthropometric variables of participants (height, weight, body mass index, 8 skinfolds, 4 diameters, and 2 perimeters) were measured. Also, their somatotype (Heat-Carter) and Yuhaz formula was used for calculating the body composition (weights and percentages of fat, bone, and muscle). In the statistical evaluation of the difference between the measurements the Kruskal Wallis test has been used. Result: The mean subject age forwards were the youngest (20.67±3.11) p<0.01. The goalkeepers were the tallest and the heaviest (184 ±8.72 cm; 84.86±12,8 kg), and had similar amounts of body fat (13.72 ±4.34% goalkeepers, 11.23±1.25% defenders, 11.61±2.75% midfielders, 11.46±1.94% forwards ; p>0.05). whereas the forwards players were shorter and lightweight than the others (177.15±4.82 cm, 73.66±4.04 kg). At all the players the highest value of the skinfold thicknesses was the Suprailiaca. The midfielders had largest calf girth (38.53±2 cm) and thinner calf skinfold thicknesses (5.94±2.58 mm). There were significant differences all groups in femur bicondul diameters forwards 9,60±0,57, midfielders 9,28±0,49, defenders 9,84±0,49, goalkeepers 10,18±0,65 (p<0.011). There was no difference between four group of players somatotype and body composition(p>0.05). References 1. T. Reilly; J. Bangsbo; A. Franks, Anthropometric and physiological predispositions for elite soccer, Journal of Sports Sciences, Volume 18, Issue 9 September 2000 , pages 669 - 683 2. Matkovic Branka R. ; Misigoj-Durakovic Marjeta ; Matkovic Bojan ; Jankovic Saga ; Ruzic Lana ; Leko Goran ; Kondric Miran, Morphological Differences Of Elite Croatian Soccer Players According To The Team Position, Collegium Antropologicum, 2003, vol. 27, pp. 167-174, Sup1. ISSN 0350-6134. 3. Mary Barth Noel, Jaci L. VanHeest, Phil Zaneteas, and Carol D. Rodgers. Body Composition in Division I Football Players.The Journal of Strength and Conditioning Research Article: (May 2003) pp. 228-237 Volume 17, Issue 2